814 GENERAL INTERNAL MEDICINE AND THE GERIATRIC MEDICINE WORKFORCE: RESULTS: OF THE RCP CENSUS AND WELLBEING SURVEY. (8th March 2022) - Welch, C; Copeland, C
Abstract: Background: In the UK, most geriatric medicine consultants also contribute to general internal medicine ('acute take') services. However, impact on workforce was unclear. Methods: We used anonymised data available from the Royal College of Physicians (RCP) 2019 census, and the RCP wellbeing snapshot survey conducted in early 2020. We used multivariable analysis of covariance (adjusting for age, gender, nation, NHS academic or other contract type, contribution to general or acute medicine services, and less than full-time working) to assess for differences in mean excess Programmed Activities (PAs) worked above contracted PAs between geriatric medicine and other physician specialties. We used binary logistic regression analysis to assess for satisfaction in own specialty and general medicine (adjusting for variables above), and in perceived excess workload and excess hours (adjusting for age, gender, and nation). Results: The RCP census included 16, 746 consultant physicians, including 1, 677 (10%) geriatricians. The wellbeing survey included 2, 670 respondents, including 343 (12.8%) geriatricians. Geriatricians reported working excess programmed activities, but fewer than other specialties (adjusted means: 0.74, CI 0.59–0.89 vs. 0.95, CI 0.82–1.07; p < 0.001). Geriatricians were also less likely to report always or often working excess hours (OR 0.61, CI 0.47–0.78; p < 0.001) or having an excess workload (OR 0.60, CI 0.47–0.78; p < 0.001). There were no differences in satisfaction with their own specialty, but geriatricians were more likely to report increased satisfaction with general medicine (OR 1.65, CI 1.30–2.09; p < 0.001). Conclusion: Physicians, in the UK, frequently report working excess hours beyond their contracted job plans. However, geriatricians report fewer excess hours than other specialties. Geriatricians also report greater perceived satisfaction working in general medicine than other physician specialties.